2012
DOI: 10.1371/journal.pone.0044002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metagenomics of Toxic Freshwater Cyanobacteria Bloom Communities on Two Continents

Abstract: Toxic cyanobacterial blooms have persisted in freshwater systems around the world for centuries and appear to be globally increasing in frequency and severity. Toxins produced by bloom-associated cyanobacteria can have drastic impacts on the ecosystem and surrounding communities, and bloom biomass can disrupt aquatic food webs and act as a driver for hypoxia. Little is currently known regarding the genomic content of the Microcystis strains that form blooms or the companion heterotrophic community associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
102
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 50 publications
8
102
0
2
Order By: Relevance
“…Our data support the idea that microbial phylogenetic diversity corresponds with functional diversity, since variation in the functional profile of microbial communities was significantly related to the potential taxonomic composition of the transcript pool (Mantel test, P Ͻ 0.0001, df ϭ 32). Previous studies have found that function was not significantly related to strain-level taxonomic composition in the open ocean and freshwater habitats, which suggested that there may be some degree of functional redundancy in bacterioplankton communities (35,68). However, the potential taxonomic changes in the transcript pool over time observed in the Chesapeake Bay were more extensive and corresponded with significant variation in functional activities.…”
Section: Discussionmentioning
confidence: 87%
“…Our data support the idea that microbial phylogenetic diversity corresponds with functional diversity, since variation in the functional profile of microbial communities was significantly related to the potential taxonomic composition of the transcript pool (Mantel test, P Ͻ 0.0001, df ϭ 32). Previous studies have found that function was not significantly related to strain-level taxonomic composition in the open ocean and freshwater habitats, which suggested that there may be some degree of functional redundancy in bacterioplankton communities (35,68). However, the potential taxonomic changes in the transcript pool over time observed in the Chesapeake Bay were more extensive and corresponded with significant variation in functional activities.…”
Section: Discussionmentioning
confidence: 87%
“…Not only do bloom-forming organisms such as Microcystis aeruginosa live in competition with other phytoplankton species, they also live in concert with heterotrophic bacteria, which can attach to the mucilaginous matrix produced by M. aeruginosa colonies (15, 16). There is a dearth of information concerning the functional role that co-occurring bacteria may play in bloom dynamics, although recent studies suggest that heterotrophs may play an important role in the metabolism of some nutrients (17, 18).As metagenomic surveys have provided new insight into the dynamics of microbial communities, a growing number have suggested that microbial community function is independent of the identity of the member organisms, including one study of a Lake Erie cHAB community (18)(19)(20). These studies, however, allow only for inference about community functional potential, as they are based on the analysis of DNA.…”
mentioning
confidence: 99%
“…Not only do bloom-forming organisms such as Microcystis aeruginosa live in competition with other phytoplankton species, they also live in concert with heterotrophic bacteria, which can attach to the mucilaginous matrix produced by M. aeruginosa colonies (15,16). There is a dearth of information concerning the functional role that co-occurring bacteria may play in bloom dynamics, although recent studies suggest that heterotrophs may play an important role in the metabolism of some nutrients (17,18).…”
mentioning
confidence: 99%
“…In a comparative study, Steffen et al highlighted the utility of Metagenomics as a tool for exploration of microbial communities, provided microbial snapshots of three separate toxic cyanobacterial blooms, Lake Erie (North America), Lake Tai (Taihu, China), and Grand Lakes, St. Marys (OH, USA), using comparative Metagenomics [21]. They concluded that despite being single samples, these metagenomes provided a unique snapshot of the microbial community associated with toxic cyanobacterial blooms.…”
Section: Microbial Community Structuresmentioning
confidence: 99%
“…The most of the lakes examined in this section 4 were associated with this genus. Lake Taihu has experienced Microcystis bloom events for decade, Xie et al [10] and Steffen et al [21] focused their studies on this lake; Cao et al [14] reported that analysis at the genus level of Cyanobacteria identified that Microcystis was among the most abundant genus in the 21 plateau lakes in Yunnan, China; Steffen et al [21] stated that Microcystis-dominated blooms had been observed in the western basin of Lake Erie annually since the 1990s; the study by Berry et al [24] in western Lake Erie also showed that Cyanobacterial community composition fluctuated dynamically during the bloom, but was dominated by Microcystis and Synechococcus OTUs; Tromas et al [25] reported that blooms in their study site (Lake Champlain, North America) tended to be dominated by one or two genera of cyanobacteria: Microcystis or Dolichospermum; in the study of Touzet [19] …”
Section: Microcystis Appears In Most Of the Studies Lakesmentioning
confidence: 99%